Role of autophagy in lipid aggregation in lipid-induced renal tubular epithelial damage - WANG Rui; ZHANG Ning (Linchuang shenzangbing zazhi)
Objective To investigate the role of autophagy in lipid aggregation in lipid-induced renal tubular epithelial damage.Methods Renal tubular epithelial cells(HK-2) were incubated with low density lipoprotein(LDL) at different concentrations(0,20 μg/ml,50 fig/ml,and 100 μg/ml)for 24 h.Lipid deposition in HK-2 cells was evaluated by oil red O stain.Autophagosomes were observed by transmission electron microscopy.The LC3-GFP fusion protein was observed by fluorescence microscope.LC3 Ⅰ/Ⅱ protein was assessed by Western blotting.Results(1)LDL stimulate HK-2 cell for 24 h at the concentration in range from 0—100 μg/ml,and we detected lipid deposition in HK-2 cell stain by oil red O.The result showed that lipid deposition increasing caused by LDL stimulating in HK-2 cell performed in a time-dependent manner.(2) Autophagosome were observed in nomal HK-2 cell by transmission electron microscopy.However,after LDL stimulation HK-2 cell,autophagosome was increased in a dose-dependent manner with the LDL at the concentration from 0 to 50 μg/ml.But,autophagosome decreased rapidly at LDL 100 μg/ml concentration.(3) Few LC3-GFP dots were present in nomal HK-2 cell in basal condition,which were detected by fluorescence microscope.However,after LDL stimulation HK-2 cell,LC3-GFP dots was increased in a dose-dependent manner with the LDL at the concentration from 0 to 50 μg/ml(P<0.05).But,LC3-GFP dots decreased rapidly at LDL 100 μg/ml concentratioa(4)Both LC3- I and LC3-Ⅱ expressed in HK-2 cell,but LC3- I expression was dominant in normal cell.After LDL at concentration range from 0—50 μg/ml stimulated HK-2 cell,both LC3-Ⅰ and LC3-Ⅱ increased gradully,but LC3-Ⅱ increased more obviously.The expression of LC3- Ⅰ in 50 μg/ml LDL treated group was 2 times as that in 0 μg/ml LDL treated group(P<0.05).But the expression of LC3-Ⅱ in 50 μg/ml LDL treated group was 3 times as that in0 μg/ml LDL treated group(P<0.05).Thus,LC3-Ⅱ/LC3-I ratio increased in a dose-dependent manner at LDL concentration range from 0 to 50 μg/ml.However,when LDL concentration increased at 100 μg/ml,both LC3- Ⅰ and LC3-Ⅱ were drastically reduced.The expression of LC3- I in 100μg/ml LDL treated group was almost equally with that in 0 μg/ml LDL treated group(P>0.05).The expression of LC3- Ⅱ in 100 μg/ml LDL treated group dropped and it is only 1.5 times as that in 0 μg/ml LDL treated group(P<0.05).LC3-II/LC3-I ratio were also declined sharply.Conclusions Autophagy may be involved in lipid-induced renal tubular epithelial damage in lipid aggregation.